Kinerja Keuangan dalam Perspektif Rasio Arus Kas Pada Perusahaan Pertambangan Study Bursa Efek Indonesia - Rahmat Hidayat (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to determine and analyze the cash flow ratio in assessing the financial performance of PT. Adaro Energy. The tools used to analyze the cash flow ratio are Operating Cash Flow Ratio (AKO), Cash Coverage Ratio to Current Liabilities (CKHL), Capital Expenditure Ratio (PM) and Total Debt Ratio (TH). Descriptive research approach, the type of data used is quantitative data, data sources used are secondary data and primary data. Data collection techniques used are documentation and interviews. The data analysis technique used is content analysis technique. Based on the results of the study, it is known that the financial performance of PT. Adaro Energi which was measured using the Operating Cash Flow Ratio (AKO) in 2014 to 2018 was not good.